2005
DOI: 10.1021/es047935q
|View full text |Cite
|
Sign up to set email alerts
|

Trace Analysis of Bromate, Chlorate, Iodate, and Perchlorate in Natural and Bottled Waters

Abstract: A simple and rapid method has been developed to simultaneously measure sub-µg/L quantities of the oxyhalide anions bromate, chlorate, iodate, and perchlorate in water samples. Water samples (10 mL) are passed through barium and hydronium cartridges to remove sulfate and carbonate, respectively. The method utilizes the direct injection of 10 µL volumes of water samples into a liquid chromatography-tandem triple-quadrupole mass spectrometry (LC-MS/MS) system. Ionization is accomplished using electrospray ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
115
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(120 citation statements)
references
References 31 publications
2
115
0
3
Order By: Relevance
“…In accordance with the ever-increasing concern regarding perchlorate in the United States, more and more reports have been published on the occurrence of perchlorate in different environmental matrices such as groundwater, milk, biological sample, et al (Krynitsky et al, 2004;Snyder et al, 2005;Valentin-Blasini et al, 2005 (Snyder et al, 2005) et al determined perchlorate in 11 different natural water bodies and 21 brand bottled drinking water, and found that there was perchlorate pollution in most samples.…”
Section: Introductionmentioning
confidence: 95%
“…In accordance with the ever-increasing concern regarding perchlorate in the United States, more and more reports have been published on the occurrence of perchlorate in different environmental matrices such as groundwater, milk, biological sample, et al (Krynitsky et al, 2004;Snyder et al, 2005;Valentin-Blasini et al, 2005 (Snyder et al, 2005) et al determined perchlorate in 11 different natural water bodies and 21 brand bottled drinking water, and found that there was perchlorate pollution in most samples.…”
Section: Introductionmentioning
confidence: 95%
“…Other reports of natural ClO4 -occurrences in the U.S. include a nitrate deposit in California (13) and potash minerals and other evaporites from California and New Mexico (14). A relatively large areal distribution of ClO4 -in west Texas groundwater (15) and groundwater, surface water, and bottled water from other areas (16) has been tentatively attributed to natural sources as well as ClO4 -in Pleistocene and Holocene groundwater in New Mexico (17).…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, several studies developed the application of reversed phase LC-ESI-MS/MS for perchlorate analysis [38][39][40].…”
mentioning
confidence: 99%